How climate-related disasters reshape tax morale in sub-Saharan Africa - Enrico Nichelatti; Abrams Mbu Enow Tagem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Climate-related disasters have increased over recent decades, with severe human and economic consequences. While research has examined their macroeconomic effects and impact on households' income and consumption patterns, little attention has been given to their impact on tax morale-taxpayers' intrinsic motivation to comply with tax obligations. This study fills this gap by estimating the impact of climaterelated disasters on tax morale in 26 sub-Saharan African countries using Afrobarometer survey data from 2011 to 2021. The analysis considers six climate-related shocks: droughts, earthquakes, extreme temperatures, floods, storms, and wildfires. We hypothesize that the impact of climate-related disasters on tax morale depends on the specific disasters considered, and that these heterogeneous effects work through two key mechanisms: economic inequality and trust in public institutions. First, they can exacerbate inequality by reducing government revenue, increasing economic hardship for vulnerable groups (through loss of livelihoods), and eliciting unequal policy responses from government. Climate-related disasters can also reduce inequality when associated with increased economic hardship for richer households (by destroying their productive assets. Second, tax morale declines when citizens perceive government responses as inadequate or unfair; conversely, it increases if citizens perceive the government to be responding adequately. Logistic regression results confirm this heterogeneity. Droughts, extreme temperatures, floods, and storms reduce tax morale, while earthquakes and wildfires increase it. Incorporating regional heterogeneity shows that the negative effects of disasters on tax morale are more profound in rural areas. Mediation analysis confirms inequality and institutional trust as key transmission channels. These findings underscore the need for inclusive tax policies and effective post-disaster governance to sustain revenue mobilization in sub-Saharan Africa.
Keywords: D63; H26; Q54; 330; climate-related disasters; economic inequality; logistic regression; sub-Saharan Africa; tax morale